2006
DOI: 10.2174/157339906777950642
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Endothelin and Insulin: Expanding Parameters of Insulin Resistance

Abstract: Since the discovery of endothelin peptides in the mid-1980s by Yanigasawa and colleagues, accumulating evidence demonstrates that these peptides may function beyond vasoconstriction. Strong epidemiologic associations between insulin resistance and increased endothelin levels or activity have been found, and these associations have prompted studies investigating the interactions of endothelin with insulin. In this review we explore the evidence for such interactions at multiple levels of physiology, ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 136 publications
(189 reference statements)
1
4
0
Order By: Relevance
“…Together with the findings of experimental trials, which reported that ET receptor blockers decrease fibrosis, it is thought that ET-1 plays an important role in liver fibrosis along with other factors. In particular, the interplay among diabetes, diabetes-related liver diseases, and ET has been documented and claimed to be pathophysiologically relevant in diabetic complications [39][40][41]. In our study, ET-1 mRNA expression in the diabetic liver increased when compared to the healthy group.…”
supporting
confidence: 46%
“…Together with the findings of experimental trials, which reported that ET receptor blockers decrease fibrosis, it is thought that ET-1 plays an important role in liver fibrosis along with other factors. In particular, the interplay among diabetes, diabetes-related liver diseases, and ET has been documented and claimed to be pathophysiologically relevant in diabetic complications [39][40][41]. In our study, ET-1 mRNA expression in the diabetic liver increased when compared to the healthy group.…”
supporting
confidence: 46%
“…Glucocorticoids increase secretion of insulin in a rat model (Sood and Ismail‐Beigi 2010) and hyperinsulinaemia has, besides the reduction in endothelial NO production, also been associated with elevated concentrations of the potent vasoconstrictor ET‐1 (Juan et al . 1999; Strawbridge et al . 2006; Tousoulis et al .…”
Section: How Might Glucocorticoids Predispose To the Development Of Lmentioning
confidence: 99%
“…The regulation of digital blood flow is, however, not simply under the control of one mediator but is due to a complex interplay between vasoconstrictors such as endothelin (ET) and vasodilators such as NO (Cardillo et al 1999;Miller et al 2002). Glucocorticoids increase secretion of insulin in a rat model (Sood and Ismail-Beigi 2010) and hyperinsulinaemia has, besides the reduction in endothelial NO production, also been associated with elevated concentrations of the potent vasoconstrictor ET-1 (Juan et al 1999;Strawbridge et al 2006;Tousoulis et al 2008). In addition, hyperinsulinaemia in both a rat model as well as in diabetic patients can lead to excess arteriovenous blood shunting as a consequence of altered vasomotor tone (Stevens et al 1991;Kihara et al 1994).…”
Section: Vascular Effects Of Glucocorticoidsmentioning
confidence: 99%
“…. Tyrosine phosphorylated IRS-1 and Cbl harbor signaling proteins involved in activation of PI3K/Akt survival pathway and F-actin polymerization, respectively (Strawbridge et al, 2006). Previous studies have shown that type 2 diabetes, obesity, metabolic syndrome X and age related insulin resistance were characterized by elevated levels of vasoactive peptide endothelin-1 (ET-1) (Sayama et al, 1999;Ferri et al, 1995;Ferri et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…. ET-1 peptide induced defects in lipid membrane, impaired PI3K signaling, reduced tyrosine phosphorylation of Cbl and F-actin polymerization as well as GLUT4 trafficking when added to insulin- or sorbitol-incubation conditions; thus, ET-1 challenges and overwrites protective role of Cbl (Strawbridge et al, 2006). Taken together, previous and our current findings suggest that under normal conditions Cbl negatively regulates p85 whereby it potentially minimizes the available PI3K pool utilized for basal signaling by RTK and non-RTK.…”
Section: Discussionmentioning
confidence: 99%